Synthesis of Mepivacaine and Its Analogues by a Continuous‐Flow Tandem Hydrogenation/Reductive Amination Strategy. Issue 44 (16th August 2017) - Suveges, Nícolas S.; de Souza, Rodrigo O. M. A.; Gutmann, Bernhard; Kappe, C. Oliver
Abstract : Herein we report a convenient, fast, and high‐yielding method for the generation of the racemic amide anaesthetics mepivacaine, ropivacaine, and bupivacaine. Coupling of α‐picolinic acid and 2, 6‐xylidine under sealed‐vessel microwave conditions generates the intermediate amide after a reaction time of only 5 min at 150 °C. Subsequent reaction in a continuous‐flow high‐pressure hydrogenator (H‐Cube Pro TM ) in the presence of the respective aldehyde directly converts the intermediate to the final amide anaesthetics in a continuous, integrated, multi‐step ring‐hydrogenation/reductive amination protocol. Merits and limitations of the protocol are discussed. Abstract : A tandem, multi‐step hydrogenation/reductive amination in a benchtop, continuous‐flow hydrogenator affords local anaesthetics of the amino amide family, such as mepivacaine, rac ‐ropivacaine, and bupivacaine, in good yields.